Pengaruh Partisipasi Anggota Kelompok Wanita Tani Terhadap Tingkat Keberdayaan - Adzani, Alifa Maula; Hamdan, Ahmad; Laksono, Bayu Adi (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
The current level of empowerment of Women Farmers Group is considered moderate, with suboptimal management and uneven skills distribution, leading to the need for active monitoring that significantly influences the empowerment level of the Women Farmers Group. Therefore, active participation is crucial, making the REBONDING program a solution to the existing issues. This research aims to explore the influence of the participation of Women Farmers Group members on the empowerment level. The study employs a correlational method with a quantitative approach. The sampling technique used is saturation sampling, involving the entire population, consisting of 30 members of the Women Farmers Group Mekar 2 in Mekarharja Village. The research instrument used is a questionnaire containing statements that have been tested for validity and reliability. The collected data underwent normality assumption testing and heteroscedasticity assumption testing, allowing for the continuation to the hypothesis testing stage, namely simple linear regression and determination analysis (R Square). The analysis results state that the contribution of the variable "participation of Women Farmers Group members" to the empowerment level is 73.5%, while the remaining 26.5% is contributed by other variables not included in the research model. In conclusion, the participation of Women Farmers Group members in the Rebo Distan Keliling program has a positive and significant impact on the empowerment level. With a probability value < alpha level of 0.05 (5%), the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.